Prospek Bisnis Budidaya Melon Inthanon Menggunakan Greenhouse (Studi Kasus Pondok Pesantren Al-Hidayat Gerning Kabupaten Pesawaran) - Kurniawati, Risma; Handayani, Sri; Noer, Irmayani; Irawati, Luluk (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Al-Hidayat Gerning Islamic boarding school is a boarding school that farms inthanon melon using a greenhouse. However, in the implementation of cultivation, the boarding school faces various challenges, such as the high price of inthanon melon seeds, limited market access, and high initial investment for green house construction. The objectives of the study were (1) to identify the costs, revenues, and profits of inthanon melon farming, (2) to analyze the feasibility of inthanon melon farming, and (3) to analyze the sensitivity of inthanon melon farming. The data analysis method is quantitative method. The results of this study (1) The business cost structure consisting of fixed costs of Rp9,908,393, variable costs of Rp11,065,350, total costs of Rp20,974,74 and revenue of Rp37,440,000 so as to get a profit of Rp16,466,257 during one planting period. (2) Financial feasibility analysis shows the NPV value of Rp231,899,623>0, IRR of 20.73%>8% interest rate, Net B/C ratio of 1.683>1, BEP of 6 years 7 months 25 days shorter than the project life of 10 years and PBP for 3 years 6 months 28 days shorter than the project life of 10 years. Based on these results, inthanon melon farming at Al-Hidayat Islamic Boarding School is feasible to run, and (3) Sensitivity analysis of a 10% increase in production costs shows an NPV value of 0.211, IRR of 0.165, and Net B/C of 0, 118. This indicates that if the sensitivity value is less than one, then the inthanon melon farming business at Al-Hidayat Islamic Boarding School is not sensitive to these changes. Meanwhile, a decrease in the price of inthanon melon by Rp25,000 shows an NPV value of 1.246, IRR 0.574 and Net B/C 0.369. This indicates that the price decrease is sensitive to NPV or future net profit because the sensitivity value is more than one.